2021
DOI: 10.1101/2021.07.11.451874
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of glioma-associated microglia and macrophages reveals their divergent roles in the immune response of brain

Abstract: Glioma microenvironment contains numerous myeloid cells, including brain-resident microglia and recruited monocytes and macrophages (Mo/Mφ). When studied collectively, these cells presented pro-tumor effects. Yet, little is known about the differences among these myeloid populations. Using single-cell sequencing analysis, we studied the phenotypic characteristics, spatial variances, and dynamic changes of these relatively heterogeneous cell populations. Microglia populations with distinct spatial distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…2). Nevertheless, Qian et al found that Crybb1 and Ldhb are specific and stable markers across different tumor stages in mice, and the cluster of MDMs consistently featured with Iqgap1 corresponded to other clinical datasets [80]. A variety of cytokines (IL-6 and IL-10) and several genes encoding chemokines associated with wound healing (Ccl22, Ccl17, Cxcl2, and Cxcl3) are upregulated in TAMs [81].…”
Section: Interactions Between Glioma and Microglia/ Macrophages Heter...mentioning
confidence: 99%
“…2). Nevertheless, Qian et al found that Crybb1 and Ldhb are specific and stable markers across different tumor stages in mice, and the cluster of MDMs consistently featured with Iqgap1 corresponded to other clinical datasets [80]. A variety of cytokines (IL-6 and IL-10) and several genes encoding chemokines associated with wound healing (Ccl22, Ccl17, Cxcl2, and Cxcl3) are upregulated in TAMs [81].…”
Section: Interactions Between Glioma and Microglia/ Macrophages Heter...mentioning
confidence: 99%
“…Altered expression of these widely used microglial markers was subsequently observed during the course of CNS diseases. P2RY12 serves as a prototypical example of altered microglial markers during brain disorders, and a decrease in its expression is a prominent feature of microglia in Alzheimer’s disease [ 137 ] and glioma [ 138 ]. Other markers for microglia in homeostatic conditions, such as Cx3cr1 , Sall1 , and Tmem119 , are also downregulated in glioma [ 138 ].…”
Section: Introductionmentioning
confidence: 99%
“…P2RY12 serves as a prototypical example of altered microglial markers during brain disorders, and a decrease in its expression is a prominent feature of microglia in Alzheimer’s disease [ 137 ] and glioma [ 138 ]. Other markers for microglia in homeostatic conditions, such as Cx3cr1 , Sall1 , and Tmem119 , are also downregulated in glioma [ 138 ]. Despite some incremental progress, a lack of widely accepted cell markers limits the functional confirmation of these two cell populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation